Heterogeneous integration of BIM with low-cost indoor mobile laser scanning method for building fabric maintenance in China - Chen, Chao (2019)
The architecture, engineering and construction (AEC) industry is one of the most energy consuming and waste producing sectors in recent decades. Now it is facing the challenges of technological innovation and structural upgrading due to the increase requirements of sustainable development such as less wastes, lower energy consumption and higher productivity. As the largest AEC market in the world, China is exploring an innovative way based on digitalization and informatization to realize sustainable development of its local AEC industry.